Identifying migratory pathways of Nathusius' pipistrelles (Pipistrellus nathusii) using stable hydrogen and strontium isotopes. (26th January 2021) - Kruszynski, Cecilia; Bailey, Liam D.; Courtiol, Alexandre; Bach, Lothar; Bach, Petra; Göttsche, Matthias; Göttsche, Michael; Hill, Reinhold; Lindecke, Oliver; Matthes, Hinrich; Pommeranz, Henrik; Popa‐Lisseanu, Ana G.; et al.
Abstract : Rationale: Identifying migratory corridors of animals is essential for their effective protection, yet the exact location of such corridors is often unknown, particularly for elusive animals such as bats. While migrating along the German coastline, Nathusius' pipistrelles ( Pipistrellus nathusii ) are regularly killed at wind turbines. Therefore, we explored the paths taken on their annual journey. Methods: We used isotope ratio mass spectrometry to measure stable hydrogen and strontium isotope ratios in fur keratin of 59 Nathusius' pipistrelles captured on three offshore islands. Samples were pre‐treated before analysis to report exclusively stable isotope ratios of non‐exchangeable hydrogen. We generated maps to predict summer origins of bats using isoscape models. Results: Bats were classified as long‐distance migrants, mostly originating from Eastern Europe. Hydrogen analysis suggested for some bats a possible Fennoscandian origin, yet additional information from strontium analysis excluded this possibility. Instead, our data suggest that most Nathusius' pipistrelles migrating along the German coastline were of continental European summer origin, but also highlight the possibility that Nathusius' pipistrelles of Baltorussian origin may travel offshore from Fennoscandia to Germany. Conclusions: Our findings demonstrate the benefit of using complementary isotopic tracers for analysing the migratory pathways of bats and also potentially other terrestrial vertebrate species. Furthermore, data from our study suggest an offset of fur strontium isotope ratios in relation to local bedrock.